Bartonella henselae Endocarditis and Glomerulonephritis with Dominant C3 Deposition in a 21-Year-Old Male with a Melody Transcatheter Pulmonary Valve: Case Report and Review of the Literature. (July 2014) - Georgievskaya, Zhanna; Nowalk, Andrew J.; Randhawa, Parmjeet; Picarsic, Jennifer
We report a case of a 21-year-old young man with underlying congenital heart disease who developed Bartonella henselae endocarditis of the right ventricular outflow tract (RVOT) conduit of his Melody transcatheter (percutaneous) pulmonary valve (TPV), with an initial presentation of glomerulonephritis with a dominant C3 pattern, with renal failure and circulating cryoglobulins. There are few reports of a glomerulonephritis with a dominant C3 pattern presenting as a manifestation of B. henselae endocarditis. While most cases of B. henselae endocarditis affect the aortic valve, in this case the valve damage was to the RVOT of the Melody TPV, a percutaneous transcatheter valve delivery system that had previously replaced his pulmonary homograft, which had become dysfunctional as a result of prior Streptococcus viridans endocarditis. The pulmonary homograft had been in place since childhood as a result of a Ross procedure to repair his congenital aortic stenosis. The patient's renal failure significantly improved after surgical resection of the infected RVOT and institution of appropriate antibiotic therapy.